Chemotherapy for Leukemia Children on Elevated Creatinine Ureum Levels - Aslinda Aslinda; Ratna Mahmud; Harmawati Harmawati; Rahdiastuti Andi Patangai; Ayuni Maulidiya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine urea and creatine levels before and after chemotherapy in childhood leukemia. The research method used in this research is Quasi Experiment Pretest-posttest research. The results of the study show that based on the univariate analysis that has been carried out, it is known that the highest age of children with leukemia is school age (6-12 years). The most common gender of childhood leukemia is male, and the most common type of childhood leukemia is Acute Lymphoblastic Leukemia (ALL). Meanwhile, in the bivariate analysis after the Wilcoxon test, the p-value of urea levels before and after chemotherapy was 0.808 > 0.05, and the p-value of creatinine levels before and after chemotherapy was 0.1000 > 0.05. In conclusion, there is no difference in urea and creatinine levels before and after chemotherapy in children with leukemia. Keywords: Chemotherapy, Ureum Creatinine, Childhood Leukemia